A Rate Control Model of MPEG-4 Encoder for Video Transmission over Wireless Sensor Network - Nor Syahidatul Nadiah, Ismail; Farizah, Yunus; Sharifah Hafizah, Syed Ariffin; Sharifah Kamilah, Syed Yusof (Institute of Information Technology, Kohat University of Science and Technology, 2019)
Recently, multimedia application has a lot of attention in the research community, especially when transmitting video over IEEE 802.15.4 standard. This is due to the capability of providing low complexity with low cost, but still maintaining the quality of video in term of packet received. However, transmitting video over Wireless Sensor Network (WSN) posed a new research challenges with high bandwidth demand and energy constrained of sensor nodes. MPEG-4 video codec is one of the compression techniques that used to decrease the amount of bandwidth required to meet WSN environment. Therefore, video encoding is a useful tool for rate control to control the video bit rate and maintaining the video quality especially in real-time communication applications. Video bit rate is affected by quantization scale, frame rate, and Group of Picture (GOP) size. A rate control model called enhanced Video Motion Classification based (e-ViMoC) model is proposed in this paper to produce the desired bit rate that complies to the IEEE 802.15.4 standard, while at the same time preserving the video quality. The analysis has shown that, the video transmission using e-ViMoC rate control achieves enhancement in delivery ratio, energy consumption and video quality (PSNR) when compared to video transmission using uncompressed video.